(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Eclipta alba Linn. (ASTERACEAE) is an annual herb, with curative properties and severely usedas analgesic, antibacterial, antioxidant and antihyperglycemic among folklore to cure various ailment. Theantibacterial studies were done by agar well diffusion methods. The MIC and MBC methods were alsoused. Hexane extract of Eclipta alba showed high antibacterial activity against S. aureus, B. cereus, E. coli,S. typhi whereas acetone, ethanol, methanol and aqueous extracts showed intermediate activity against S.aureus, B. cereus, E. coli and S. typhi.